1999
DOI: 10.1073/pnas.96.10.5862
|View full text |Cite
|
Sign up to set email alerts
|

Genetic engineering of the unsaturation of fatty acids in membrane lipids alters the tolerance ofSynechocystisto salt stress

Abstract: The role of unsaturated fatty acids in membrane lipids in the tolerance of the photosynthetic machinery to salt stress was studied by comparing the desA ؊ ͞desD ؊ mutant of Synechocystis sp. PCC 6803, which contained monounsaturated fatty acids, with the wild-type strain, which contained a full complement of polyunsaturated fatty acids. In darkness, the loss of oxygen-evolving photosystem II activity in the presence of 0.5 M NaCl or 0.5 M LiCl was much more rapid in desA ؊ ͞desD ؊ cells than in wild-type cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(126 citation statements)
references
References 24 publications
5
121
0
Order By: Relevance
“…After 1.2 h of salt shock, much higher Na ϩ exclusion activity was observed for the ApNhaP-expressing cells than for the control cells after the addition of diethanolamine, i.e., 75% vs. 30% during 15 min (data not shown). Salt stress has been shown to impair photosynthetic activity in a number of photosynthetic organisms (7,11,14). To determine whether the expression of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 1.2 h of salt shock, much higher Na ϩ exclusion activity was observed for the ApNhaP-expressing cells than for the control cells after the addition of diethanolamine, i.e., 75% vs. 30% during 15 min (data not shown). Salt stress has been shown to impair photosynthetic activity in a number of photosynthetic organisms (7,11,14). To determine whether the expression of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these toxic effects, salt stress induces oxidative stress (4). Considerable efforts to improve the salt tolerance of plants by genetic engineering techniques have been made (5)(6)(7)(8)(9)(10)(11). But, those achievements are not satisfactory (12).…”
Section: Aphanothece Halophytica ͉ Genetic Engineeringmentioning
confidence: 99%
“…Light-dependent inactivation of photosynthesis, termed photoinhibition, is often observed under a variety of environmental stresses, including high-intensity light (Allakhverdiev et al, 1999;Hideg et al, 2000;Trebst et al, 2002; for review, see Aro et al, 1993, and refs. therein).…”
Section: Oxidative Stress Is Unlikely To Be the Cause Of Glc Lethalitmentioning
confidence: 99%
“…The gene for desaturation of fatty acids (desA) is also unique to C. caldarium. Recently it was shown that desA is important for the tolerance of the photosynthetic machinery to salt stress (Allakhverdiev et al 1999).…”
Section: Unique C Caldarium Genes With Known Functionsmentioning
confidence: 99%